THE RELATIONSHIP BETWEEN WORK OPTIONS TOWARDS EMPLOYEE ENGAGEMENT DURING COVID-19 PANDEMIC IN SIBU - Belinda Swee Bing, Chiong (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study aims to examine the relationship between work options and employee engagement (motivation, stress, and productivity) during COVID-19 pandemic in Sibu. Questionnaire surveys were administered to administrative staff in private company in Sibu with 50 questionnaires collected. The respondents were categorised into 2 groups (work from home group and work from office group) with 25 respondents in each group. Mann-Whitney U Test was used to test the hypotheses and the results show that the work options do not have significant effect in neither in improving the employee engagement nor declining the employee engagement. Kelley’s Covariation Attribution theory was used in this study to explain the situation. The findings of the study may contribute useful information and body of knowledge for both HR practitioners and future researchers for the purpose of improving current policy on coping with COVID19 pandemic.